2008
DOI: 10.1111/j.1445-2197.2008.04567.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surgical Performance Using V‐possum Risk‐adjusted Mortality Rates

Abstract: Vascular-Physiological and Operative Severity Score for the enUmeration of Mortality and Morbidity (V-POSSUM) is a risk-adjusted scoring system for predicting 30-day mortality in patients undergoing vascular surgery. It can assess surgical performance by comparing predicted deaths with observed deaths. The aim of this analysis was to assess trends in surgical performance over time using risk-adjusted 30-day mortality as the primary outcome. Major vascular surgery procedures (n = 454) were prospectively scored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…For all other models the inclusion of intraoperative data represented an enormous limitation as prognostic scores and some authors considered that it makes scores neither simple or rapid to use. (16,23) Complex tools are not necessarily associated to better discrimination for risk prediction (6) and are difficult to apply on daily practice. (14) On the other hand, POSSUM models are widely available as they can be calculated by free online calculators.…”
Section: Resultsmentioning
confidence: 99%
“…For all other models the inclusion of intraoperative data represented an enormous limitation as prognostic scores and some authors considered that it makes scores neither simple or rapid to use. (16,23) Complex tools are not necessarily associated to better discrimination for risk prediction (6) and are difficult to apply on daily practice. (14) On the other hand, POSSUM models are widely available as they can be calculated by free online calculators.…”
Section: Resultsmentioning
confidence: 99%
“…The POSSUM score had initially been developed by Copelan et al to serve as a scoring system for surgical audit [1]. Following his publication, various modifications were made to adapt it to the needs of different fields in surgery, among them vascular [2], gastrointestinal [3], urologic [4] and orthopaedic [5]. The POSSUM score was further modified to adapt it for patients with proximal femur fractures who comprise a difficult at-risk group [6][7][8], For example, Ramanathan et al [6] found that POSSUM over-predicts mortality in proximal femur fracture patients and recommended that it should be used with caution, whether as an audit tool or for preoperative triage.…”
Section: Tablementioning
confidence: 99%
“…These 12-variable factors, 4-grade physiologic and 6 operative-factor score were developed for the general spectrum of vascular, gastrointestinal, hepatobiliary, urological and miscellaneous surgeries. Various modifications of the original form were made to provide better prediction for different groups of patients, i.e., P-POSSUM (Portsmouth) [2], V-POSSUM (vascular) [3], and CR-POSSUM (colorectal) [4]. Mohamed et al [5] developed an orthopaedic version using a modified operation classification.…”
mentioning
confidence: 99%
“…It has been used to assess surgical performance by comparing predicted deaths with observed deaths. 11,12 There is, however, no consensus on the best risk prediction model for mortality following elective abdominal aortic aneurysm repair. A recent analysis of 5 risk prediction models has been undertaken by using the UK National Vascular Database.…”
Section: Article See P 2707mentioning
confidence: 99%